Manifestations of conflict in Al-Akhtal’s poetry - مهنّا, مها; نزيهة طه; وفاء جمعة (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
In this research, we shed light on some scenes of conflict in the poetry of Al-Akhtal Al-Taghlabi, as he is an incomparable poet who can explore his scenes in a visionary entity, filled with poetry. Conflict is a state that a person experiences as a result of the difference between his morals, religion, and ideas and the living reality. Al-Akhtal is one of the poets who experienced this conflict as a result of many reasons. He is of a different religion, different mentality, and affiliation, and this is what appeared in his poetry in multiple aspects. The religious conflict appears through the remnants of the poem in the self, and the framing of the tendencies of this conflict between instincts and their inhibitors, and between worldly and religious matters, and we find the cultural conflict represented by the difference in ideologies and intellectual matters that radiate thought and the glows of Arab civilization. The social conflict manifested itself in the class struggle between the rich and the poor, between officials of authority and the general public, and between the various societal forces that had their presence and influence in Arab life in general. The political conflict was the voice of the citizen against the forces that hindered his progress.